Global Authoritarianism Perspectives and Contestations from the South (Edition Politik, 2022)
We are witnessing a worldwide resurgence of reactionary ideologies and movements, combined with an escalating assault on democratic institutions and structures. Nevertheless, most studies of these phenomena remain anchored in a methodological nationalism, while comparative research is almost entirely limited to the Global North. Yet, authoritarian transformations in the South - and the struggles against them - have not only been just as dramatic as those in the North but also preceded them, and consequently have been studied by Southern scholars for many years. This volume brings together the work of more than 15 scholar-activists from across the Global South, combining in-depth studies of regional processes of authoritarian transformation with a global perspective on authoritarian capitalism. With a foreword by Verónica Gago.